Foaming ceramic with whole-body ion coloring and preparation method and application thereof
By using lithium tailings and ceramic processing solid waste combined with metal oxide ion coloring technology, high-strength, beautiful colored foamed ceramics are prepared, which solves the problem of traditional foamed ceramics in architectural decoration and ancient building restoration. The shortcomings have achieved environmental protection and cost reduction effects.
Patent Information
- Application Number
- CN202411713236.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
Traditional foamed ceramics are difficult to meet the requirements of color and strength in the interior and exterior decoration of buildings and the restoration of ancient buildings, and at the same time, they are costly and unfriendly to the environment.
Lithium tailings and ceramic processing solid waste are used as the main raw materials, combined with metal oxides as colorants, and ionic ion-colored foamed ceramics with high compressive strength and uniform color are prepared through ionic chromatography.
It realizes the high strength and beautiful color of foamed ceramics, is suitable for building exterior wall decoration and ancient building restoration, while reducing production costs and realizing the recycling of waste, and is environmentally friendly and ecologically friendly.
Smart Images

Figure CN119490345A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of foamed ceramics, and in particular to a foamed ceramic with whole body ion coloring, a preparation method and an application thereof. Background Art
[0002] With the promotion of green building and building energy-saving policies in my country, the research on foamed ceramic materials has remained hot. At present, the research and production technology of foamed ceramic tiles has basically reached a stable level. Traditional foamed ceramics are widely used in the field of thermal insulation. There are not many requirements on the color of the bricks, and the strength is poor, with a compressive strength of about 10Mpa.
[0003] Most of the ceramics used for interior and exterior decoration of buildings are glazed ceramic tiles, which have a more complicated production process and require at least two firings. The main production pigments are feldspar, quartz and clay, etc. The production cost is significantly higher than foam ceramic tiles. In addition, the national standard requires the compressive strength of ceramic tiles for interior and exterior decoration of buildings to be 35Mpa.
[0004] Therefore, when traditional foamed ceramics are used as building materials for interior and exterior decoration of buildings or restoration of ancient buildings, both the color and strength are difficult to meet the requirements. Summary of the invention
[0005] In view of this, the present invention provides a foamed ceramic with full-body ion coloring and a preparation method thereof. The main raw materials of the foamed ceramic are lithium tailings and solid waste generated by ceramic processing, and the colorant is a metal oxide. The ion coloring can make the brick body uniform and beautiful in color. At the same time, it has the strength of ordinary ceramic bricks and can be used for building exterior wall decoration, ancient building repair, etc. In addition, it can also realize the recycling of waste and improve the effective utilization rate of environmental resources.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In the first aspect, the present invention provides a foamed ceramic with ion coloring throughout the body, comprising the following raw materials in weight percentage: 40-70% lithium tail mud, 0-16% foamed ceramic waste powder, 0-6% foamed ceramic cutting material (black), 3-20% magnesia clay, 12-22% foamed ceramic cutting material (white), 0.1-0.8% silicon carbide, and 0.1-15% colorant; the colorant is a metal oxide, which can be Fe2O3, CuO, Co2O3, TiO2, Cr2O3, etc., and can be one or a combination of two or even more than three thereof. Those skilled in the art can combine the colors according to the needs.
[0008] When the colorant is Fe2O3, in some preferred embodiments, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-70%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-6%, magnesia clay 4-16%, foamed ceramic cutting material (white) 12-22%, silicon carbide 0.1-0.35%, Fe2O3 1-15%. Further preferably, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-62%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-6%, magnesia clay 4-16%, foamed ceramic cutting material (white) 12-22%, silicon carbide 0.1-0.35%, Fe2O3 1-15%.
[0009] When the colorant is TiO2, in some preferred embodiments, the foamed ceramic is made of the following raw materials in weight percentage: lithium tailing mud 40-70%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-6%, magnesia clay 4-16%, foamed ceramic cutting material (white) 12-22%, silicon carbide 0.1-0.35%, Zehua tailings 0-4%, TiO2 1-10%. Further preferably, the foamed ceramic is made of the following raw materials in weight percentage: lithium tailing mud 40-70%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-5%, magnesia clay 8-16%, foamed ceramic cutting material (white) 15-22%, silicon carbide 0.1-0.35%, Zehua tailings 0-4%, TiO2 1.5-10%.
[0010] When the colorant is CuO, in some preferred embodiments, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-70%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-6%, magnesia clay 4-16%, foamed ceramic cutting material (white) 12-22%, silicon carbide 0.1-0.35%, CuO 0.5-3%. Further preferably, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-50%, foamed ceramic waste powder 14-16%, foamed ceramic cutting material (black) 4-6%, magnesia clay 14-16%, foamed ceramic cutting material (white) 16-22%, silicon carbide 0.3-0.35%, CuO 0.5-3%.
[0011] When the colorant is Cr2O3, in some preferred embodiments, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-70%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-6%, magnesia clay 4-16%, foamed ceramic cutting material (white) 12-22%, silicon carbide 0.1-0.35%, Cr2O3 0.5-2%. Further preferably, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40%-50%, foamed ceramic waste powder 14-16%, foamed ceramic cutting material (black) 4-6%, magnesia clay 14%-16%, foamed ceramic cutting material (white) 16-22%, silicon carbide 0.1-0.35%, Cr2O3 1-2%.
[0012] When the colorant is Co2O3, in some preferred embodiments, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-70%, foamed ceramic waste powder 0-16%, foamed ceramic cutting material (black) 0-6%, magnesia clay 4-16%, foamed ceramic cutting material (white) 12-22%, silicon carbide 0.1-0.35%, Co2O3 0.3-2%. Further preferably, the foamed ceramic is made of the following raw materials in weight percentage: lithium tail mud 40-50%, foamed ceramic waste powder 14-16%, foamed ceramic cutting material (black) 4-6%, magnesia clay 14-16%, foamed ceramic cutting material (white) 16-22%, silicon carbide 0.1-0.35%, Co2O3 0.3-2%.
[0013] The present invention also provides a method for preparing the above-mentioned foamed ceramic, comprising the following steps:
[0014] S1: ball-milling and mixing the raw materials in the formula amount to prepare a slurry, and then spray-granulating the slurry to obtain a dry powder;
[0015] S2: putting the dry powder into a mold, and preparing the foamed ceramic through a high-temperature firing, wherein the highest firing temperature is 1160°C-1170°C.
[0016] In some preferred embodiments, in step S1, the ball milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 1.8 to 2: 1, and the ball milling time is 6-13 hours.
[0017] In some preferred embodiments, in step S2, the firing temperature rising process is: from room temperature to 920-950°C at a rate of 4-8°C / min, keeping warm for 10 minutes, then heating to 1160-1170°C at a rate of 1.0-1.5°C / min, keeping warm for 30 minutes, and finally stopping the firing and cooling naturally; the firing time is 6-7 hours.
[0018] The present invention also provides the use of the foamed ceramic in building interior and exterior decorative materials or ancient building repair materials.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The foamed ceramics of the present invention select suitable main raw materials, and the foamed ceramics obtained after firing have light compressive strength and good flexural strength, especially the compressive strength can reach more than 50Mpa, and the flexural strength can reach more than 10Mpa. Compared with traditional foamed ceramics, the strength is greatly improved and is suitable for building exterior wall decoration, ancient building restoration, etc.
[0021] 2. The foamed ceramics produced by the present invention are colored in different colors throughout the body, and the coloring is uniform. The final coloring effect can be adjusted by changing the amount of colorant in the formula. Foamed ceramics of desired colors can be produced according to actual needs and used in different scenarios.
[0022] 3. The foaming effect of the present invention can be adjusted by the content of colorant and foaming agent, the pore size can be adjusted, the pore size of the obtained foamed ceramic is uniform, and the volume density is 400-900kg / m 3 , product quality is better.
[0023] 4. The foamed ceramic raw materials of the present invention are mainly lithium tail mud and solid waste generated by ceramic processing, which can effectively reduce production costs, realize waste recycling, and is green, environmentally friendly, eco-friendly, and non-toxic. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the firing effect of the foamed tile according to Example 1 of the present invention;
[0025] Figure 2 This is a schematic diagram of the firing effect of the foamed tile according to Example 2 of the present invention;
[0026] Figure 3 This is a schematic diagram of the firing effect of the foamed tile according to Example 3 of the present invention;
[0027] Figure 4 This is a schematic diagram of the firing effect of the foamed tile according to Example 4 of the present invention;
[0028] Figure 5 This is a schematic diagram of the firing effect of the foamed tile of Example 5 of the present invention. DETAILED DESCRIPTION
[0029] In order to more clearly illustrate the purpose and technical advantages of the present invention, the present invention is further described in conjunction with the following embodiments. Obviously, the embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without making creative work are all within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0030] The specific chemical compositions of the raw materials for preparing the foamed ceramics in the following examples are provided in Table 1 below (in terms of mass percentage, in %).
[0031] Table 1 Chemical composition of raw materials used in the embodiments of the present invention
[0032]
[0033]
[0034] Note: The chemical composition of the raw materials in the above table is less than 100%, mainly due to the presence of other undetected impurities or other elements.
[0035] Embodiment 1:
[0036] This embodiment provides a series of wine red foam ceramics, the colorant is Fe2O3, the specific embodiment formula is shown in Table 2 (in mass percentage, unit is %), and the preparation method thereof comprises the steps of:
[0037] S1: First, the raw materials in the formula are ball-milled and mixed to prepare a slurry. The ball-milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 1.9: 1, the ball-milling time is 10 hours, and then the slurry is spray-granulated to obtain a dry powder.
[0038] S2 puts the dried powder into the mold for firing. The maximum firing temperature is 1165℃ and the firing time is 6.3 hours. The firing process is: heating from room temperature to 940℃ at a rate of 6℃ / min, keeping warm for 10 minutes, then heating to 1165℃ at a rate of 1.2℃ / min, keeping warm for 30 minutes, and finally stopping the firing and cooling naturally before taking out.
[0039] Table 2 Example 1 Formula Table
[0040] Example 1-1 1-2 1-3 1-4 1-5 1-6 1-7 1-8 1-9 Lithium tailings 47.07 46.14 44.82 43.18 41.28 43.91 46.26 52.75 60.94 Foamed ceramic waste powder 15.02 14.73 14.31 13.78 13.18 13.17 13.16 13.19 / Foam ceramic cutting material (black) 5.01 4.91 4.77 4.59 4.39 4.39 4.39 / / Magnesia soil 15.02 14.73 14.31 13.78 13.17 10.58 9.97 4.99 4.00 Foam ceramic cutting material (white) 16.53 16.20 15.74 15.16 14.49 14.47 12.96 15.98 21.97 SiC 0.35 0.34 0.33 0.32 0.31 0.31 0.30 0.10 0.10 <![CDATA[Fe2O3]]> 1.00 2.95 5.72 9.19 13.18 13.17 12.96 12.99 12.99
[0041] The overall color of the foamed ceramic prepared in the above embodiment is wine red, and the coloring effect varies with different formulas. Figure 1This is a picture of the foamed ceramic obtained in one embodiment after firing.
[0042] Comparative Example 1:
[0043] Comparative Example 1 has the same basic formula as Examples 1-9. In order to highlight the effect of the foaming agent SiC on the foaming pore size, bulk density, compressive strength and flexural strength of the foamed ceramic, different contents of SiC were added respectively. When the preparation process and the content of other raw materials remain unchanged, the process performance of the produced foamed ceramics is compared. The specific test results are shown in the following table:
[0044] Table 3 Comparison of foamed ceramic properties between comparative example 1 and example 1
[0045]
[0046] It can be seen from the performance test results of each group of the above comparative examples that the foamed ceramics prepared in the embodiments of the present invention have good compressive strength and flexural strength, and the amount of SiC has a direct impact on the foaming pore size, volume density, compressive strength and flexural strength of the foamed ceramics. The larger the amount of SiC added, the larger the pore size of the foamed ceramic, the smaller the volume density, and the lower the strength. When the amount of SiC is less than 0.1%, the pore size is small, but the density is large; when the SiC content is greater than or equal to 0.45%, the compressive strength and flexural strength are significantly reduced. Therefore, preferably, the SiC content is between 0.1 and 0.35.
[0047] Embodiment 2:
[0048] This embodiment provides a series of gray foam ceramics, the colorant is TiO2, the specific embodiment formula is shown in Table 4 (in mass percentage, unit is %), and the preparation method thereof comprises the steps of:
[0049] S1: First, the raw materials in the formula amount are ball-milled and mixed to prepare a slurry. The ball-milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 1.8: 1, the ball-milling time is 11 hours, and then the slurry is spray-granulated to obtain a dry powder.
[0050] S2 puts the dried powder into a mold and fires it. The maximum firing temperature is 1165℃ and the firing time is 6.3 hours. The firing process is: heat up from room temperature to 940℃ at a rate of 6℃ / min, keep warm for 10 minutes, then heat up to 1165℃ at a rate of 1.2℃ / min, keep warm for 30 minutes, and finally stop firing, cool naturally and take it out.
[0051] Table 4 Example 2 Formula Table
[0052] Example 2-1 2-2 2-3 2-4 2-5 2-6 2-7 2-8 2-9 Lithium tailings 64.58 66.39 65.04 59.32 59.94 46.63 45.26 44.01 43.2 Foamed ceramic waste powder / / / / / 14.88 14.44 14.05 13.79 Foam ceramic cutting material (black) / / / / / 4.96 4.82 4.68 4.6 Magnesia soil 8.07 8.3 8.13 15.61 15.77 14.88 14.44 14.04 13.78 Foam ceramic cutting material (white) 20.18 20.75 20.33 20.81 21.03 16.37 15.89 15.45 15.16 Zehua tailings 3.03 0.31 0.3 / / / / / / SiC 0.1 0.1 0.1 0.1 0.11 0.3 0.34 0.28 0.28 <![CDATA[TiO2]]> 4.04 4.15 6.1 4.16 3.15 1.98 4.81 7.49 9.19
[0053] The overall color of the foamed ceramic prepared in the above embodiment is blue-gray, and the coloring effect varies with different formulations. Figure 2 This is a picture of the foamed ceramic obtained in one embodiment.
[0054] Embodiment 3:
[0055] This embodiment provides a series of light red foamed ceramics, the colorant is CuO, the specific embodiment formula is shown in Table 5 (in mass percentage, unit is %), and the preparation method thereof comprises the steps of:
[0056] S1: First, the raw materials in the formula are ball-milled and mixed to prepare a slurry. The ball-milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 2.0: 1, the ball-milling time is 12 hours, and then the slurry is spray-granulated to obtain a dry powder.
[0057] S2 puts the dried powder into the mold for firing. The maximum firing temperature is 1170℃ and the firing time is 7 hours. The firing process is: heating from room temperature to 950℃ at a rate of 5.8℃ / min, keeping warm for 10 minutes, then heating to 1170℃ at a rate of 1℃ / min, keeping warm for 30 minutes, and finally stopping the firing and cooling naturally before taking out.
[0058] Table 5 Example 3 Formula Table
[0059] Example 3-1 3-2 3-3 3-4 3-5 3-6 Lithium tailings 47.31 47.07 46.84 46.61 46.37 46.14 Foamed ceramic waste powder 15.1 15.02 14.95 14.87 14.8 14.73 Foam ceramic cutting material (black) 5.03 5.01 4.98 4.96 4.93 4.91 Magnesia soil 15.1 15.02 14.95 14.87 14.8 14.73 Foam ceramic cutting material (white) 16.61 16.53 16.44 16.36 16.28 16.2 SiC 0.35 0.35 0.35 0.35 0.35 0.34 CuO 0.5 1 1.49 1.98 2.47 2.95
[0060] The foamed ceramic prepared in the above embodiment has a light red color overall. The coloring effect varies with the different CuO contents. In addition, it is found in the experiment that CuO has a certain fluxing effect. The higher the content, the larger the foaming pore size of the brick body, and the lower the body density and strength. Therefore, the CuO addition amount is limited to 0.5-3%.
[0061] Figure 3 This is a picture of the foamed ceramic obtained in one embodiment.
[0062] Embodiment 4:
[0063] This embodiment provides a series of green foamed ceramics, the colorant is Cr2O3, the specific embodiment formula is shown in Table 6 (in mass percentage, unit is %), and the preparation method thereof comprises the steps of:
[0064] S1: First, the raw materials in the formula are ball-milled and mixed to prepare a slurry. The ball-milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 2.0: 1, the ball-milling time is 12 hours, and then the slurry is spray-granulated to obtain a dry powder.
[0065] S2 puts the dried powder into the mold for firing. The maximum firing temperature is 1170℃ and the firing time is 6.4 hours. The firing process is: heating from room temperature to 950℃ at a rate of 5.8℃ / min, keeping warm for 10 minutes, then heating to 1170℃ at a rate of 1.2℃ / min, keeping warm for 30 minutes, and finally stopping the firing and cooling naturally before taking out.
[0066] Table 6 Example 4 Formula Table
[0067] Example 4-1 4-2 4-3 4-4 Lithium tailings 47.31 47.07 46.84 46.61 Foamed ceramic waste powder 15.1 15.02 14.95 14.87 Foam ceramic cutting material (black) 5.03 5.01 4.98 4.96 Magnesia soil 15.1 15.02 14.95 14.87 Foam ceramic cutting material (white) 16.61 16.53 16.44 16.36 SiC 0.35 0.35 0.35 0.35 <![CDATA[Cr2O3]]> 0.5 1 1.49 1.98
[0068] The foamed ceramic prepared in the above embodiment has an overall green color, and the coloring effect varies with the content of Cr2O3. Figure 4 This is a picture of the foamed ceramic obtained in one embodiment.
[0069] Embodiment 5:
[0070] This embodiment provides a series of blue foamed ceramics, the colorant is Co2O3, the specific embodiment formula is shown in Table 7 (in mass percentage, unit is %), and the preparation method thereof comprises the steps of:
[0071] S1: First, the raw materials in the formula are ball-milled and mixed to prepare a slurry. The ball-milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 2.0: 1, the ball-milling time is 12 hours, and then the slurry is spray-granulated to obtain a dry powder.
[0072] S2 puts the dried powder into the mold for firing. The maximum firing temperature is 1160℃ and the firing time is 6.2 hours. The firing process is: heating from room temperature to 950℃ at a rate of 5.8℃ / min, keeping warm for 10 minutes, then heating to 1160℃ at a rate of 1.2℃ / min, keeping warm for 30 minutes, and finally stopping the firing and cooling naturally before taking out.
[0073] Table 7 Example 5 Formula Table
[0074] Example 5-1 5-2 5-3 5-4 Lithium tailings 47.41 47.07 46.84 46.61 Foamed ceramic waste powder 15.13 15.02 14.95 14.87 Foam ceramic cutting material (black) 5.04 5.01 4.98 4.96 Magnesia soil 15.13 15.02 14.95 14.87 Foam ceramic cutting material (white) 16.64 16.53 16.44 16.36 SiC 0.35 0.35 0.35 0.35 <![CDATA[Co2O3]]> 0.3 1 1.49 1.98
[0075] The foamed ceramic prepared in the above embodiment has an overall blue color, and the coloring effect varies with the content of Co2O3. Figure 5 This is a picture of the foamed ceramic obtained in one embodiment.
[0076] Although only a single metal oxide colorant is given as an example in the above embodiments, it is not difficult for a person skilled in the art to understand that in order to obtain a foamed ceramic of a desired color, different metal oxides can be combined, which can be one, two, or more combinations, to obtain a foamed ceramic of a desired color.
[0077] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A foamed ceramic with ion coloring throughout, characterized in that: The invention comprises the following raw materials in percentage by weight: 40-70% of lithium tail mud, 0-16% of foamed ceramic waste powder, 0-6% of foamed ceramic cutting material (black), 3-20% of magnesia clay, 12-22% of foamed ceramic cutting material (white), 0.1-0.8% of silicon carbide and 0.1-15% of colorant; the colorant is a metal oxide, and the metal oxide is at least one of Fe2O3, CuO, Co2O3, TiO2 and Cr2O3.
2. The foamed ceramic according to claim 1, characterized in that: The invention is made of the following raw materials in percentage by weight: 40-70% of lithium tail mud, 0-16% of foamed ceramic waste powder, 0-6% of foamed ceramic cutting material (black), 4-16% of magnesia clay, 12-22% of foamed ceramic cutting material (white), 0.1-0.35% of silicon carbide and 1-15% of Fe2O3.
3. The foamed ceramic according to claim 1, characterized in that: It is made of the following raw materials in percentage by weight: 40-70% of lithium tailings, 0-16% of foamed ceramic waste powder, 0-6% of foamed ceramic cutting material (black), 4-16% of magnesia clay, 12-22% of foamed ceramic cutting material (white), 0.1-0.35% of silicon carbide, 0-4% of Zehua tailings, and 1-10% of TiO2.
4. The foamed ceramic according to claim 1, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 40-70% of lithium tail mud, 0-16% of foamed ceramic waste powder, 0-6% of foamed ceramic cutting material (black), 4-16% of magnesia clay, 12-22% of foamed ceramic cutting material (white), 0.1-0.35% of silicon carbide and 0.5-3% of CuO.
5. The foamed ceramic according to claim 1, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 40-70% of lithium tail mud, 0-16% of foamed ceramic waste powder, 0-6% of foamed ceramic cutting material (black), 4-16% of magnesia clay, 12-22% of foamed ceramic cutting material (white), 0.1-0.35% of silicon carbide and 0.5-2% of Cr2O3.
6. The foamed ceramic according to claim 1, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 40-70% of lithium tail mud, 0-16% of foamed ceramic waste powder, 0-6% of foamed ceramic cutting material (black), 4-16% of magnesia clay, 12-22% of foamed ceramic cutting material (white), 0.1-0.35% of silicon carbide and 0.3-2% of Co2O3.
7. The method for preparing the foamed ceramic according to any one of claims 1 to 6, characterized in that: The steps include: S1: ball-milling and mixing the raw materials in the formula amount to prepare a slurry, and then spray-granulating the slurry to obtain a dry powder; S2: the dry powder is loaded into a mold, and the foamed ceramic is prepared through a high-temperature firing, wherein the highest firing temperature is 1160°C-1170°C.
8. The preparation method according to claim 7, characterized in that: In the step S1, the ball milling method is wet grinding, the grinding medium is water, the material: ball: water = 1: 1.8 to 2: 1, and the ball milling time is 6-13 hours.
9. The preparation method according to claim 7, characterized in that: In step S2, the firing temperature rising process is: from room temperature to 920-950°C at a rate of 4-8°C / min, keeping warm for 10 minutes, then heating to 1160-1170°C at a rate of 1.0-1.5°C / min, keeping warm for 30 minutes, and finally stopping the firing and cooling naturally; the firing time is 6-7 hours.
10. Use of the foamed ceramic according to any one of claims 1 to 6 and the foamed ceramic prepared by the preparation method according to any one of claims 7 to 9 in building interior and exterior decorative materials or ancient building restoration materials.